Influenza neuraminidase mutations and resistance to neuraminidase inhibitors - Jiapeng Xu; Qiting Luo; Yuanyuan Huang; Jieyu Li; Wei Ye; Ran Yan; Xinrui Zhou; Zhendan He; Ge Liu; Qinchang Zhu (Emerging Microbes and Infections, 2024)
Mutations in influenza virus neuraminidase (NA) can lead to viral resistance to NA inhibitors (NAIs). To update global influenza NA mutations and resistance to NAIs, we investigated epidemic information from global regions for NAIs-resistant influenza strains and analyzed their NA mutations. Drug-resistant mutations in NA, especially new mutations occurred in 2016-2024, were updated. The H274Y mutation in N1, a major contributor to NAI resistance, peaked in 2008, significantly impacting public health in countries like Japan and the USA. Three main mechanisms of NAI resistance were identified: catalytic site mutations, structural hindrance, and monomer stability changes. Although global resistance rates of H1N1pdm09, H3N2, and influenza B have remained stable at around 1%, sporadic emergence of resistant strains highlights the need for continued vigilance. The evolution of drug-resistant, transmissible strains through compensatory mutations underscores the urgency of new antiviral strategies. Strengthening global surveillance and adjusting public health policies, such as improving vaccine coverage and prudent antiviral use, remain essential to mitigating future risks.